Hugo Chávez i opozycja - wojna medialna w Wenezueli (Świat Idei i Polityki, 2006)
When in 1998 Hugo Chávez became a president of the country, Venezuela entered into a new period in his newest history. Its society was divided into two groups: one that supports the new president and his ideology, defined as "Socialism of the XXI Century", and the other that represents the liberal values. This ideological conflict (simplifying: the poor versusteh capitalists) would not be possible without media participation. Hugo Chávez uses for his purposes above all the state media, that is tv station VTV (Venezolana de Televisión) and the radio station RNV (Radio Nacional de Venezuela). Every Sunday VTV and RNV broadcast "Aló, Presidente" - a programme of several hours, in which the president of Venezuela comments events, meets people (e.g. Fidel Castro), opens dialoque with compatriots (visits farmers, soldiers, people suffering in hospitals or youth in schools). Private tv stations present another vision of the world, alike the biggest dailies in the country, that is .El Nacional. and the liberal "El Universal". Hugo Chávez tries to silence the opposition tv stations, encountering, however, a strong resistance on their part. And the comments that you can read on the columns of the "El Universal" daily emphasize the liberals. extreme negative valuation of Chávez.s rule.